Evaluation of Wild Lentil Species as Genetic Resources to Improve Drought Tolerance in Cultivated Lentil - Gorim, Linda Y.; Vandenberg, Albert (Frontiers in Plant Science, 2017)
Abstract Increasingly unpredictable annual rainfall amounts and distribution patterns have far reaching implications for pulse crop biology. Seedling and whole plant survival will be affected given that water is a key factor in plant photosynthesis and also influences the evolving disease spectrum that affects crops. The wild relatives of cultivated lentil are native to drought prone areas, making them good candidates for the evaluation of drought tolerance traits. We evaluated root and shoot traits of genotypes of cultivated lentil and five wild species grown under two water deficit regimes as well as fully watered conditions over a 13 week period indoors. Plants were grown in sectioned polyvinyl chloride (PVC) tubes containing field soil from the A, B, and C horizons. We found that root distribution into different soil horizons varied among wild lentil genotypes. Secondly, wild lentil genotypes employed diverse strategies such as delayed flowering, reduced transpiration rates, reduced plant height and deep root systems to either escape, evade or tolerate drought conditions. In some cases, more than one drought strategy was observed within the same genotype. Sequence based classification of wild and cultivated genotypes did not explain patterns of drought response. The environmental conditions at their centers of origin may explain the patterns of drought strategies observed in wild lentils. The production of numerous small seeds by wild lentil genotypes may have implications for yield improvement in lentil breeding programs.